Maize hybrids affect a quantity of ethanol produced in the closure of Centro-Oeste paulista - do Valle Lozano, Eduardo; Nogueira, Lucas Conegundes; Alcântara, Giovanni Uema; Gravatim Costa, Gustavo Henrique [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
The Brazilian sugarcane industry has been using corn for the production of ethanol because it has a 120 day vegetative cycle, cultivation in sugarcane renovation areas, and its grains can be stored for long periods of time. In this sense, the objective of the research was to evaluate the agronomic characteristics of three corn hybrids, and the grain processing reflexes for ethanol production. The experiment was installed in the experimental farm of the Sacred Heart University (USC) located in the municipality of Agudos in the State of São Paulo in the 2016/2017 harvest. The experimental area was 8000m2, with 16 plots of 450m2 each. Hybrids 2B810PW, 2B633PW and 2B587PW were used. The planting was carried out in October 2016 and the harvest occurred at 150 days after sowing (d.a.s.). During development of the culture (45, 75, 90 and 110 d.a.s.) the biometric parameters were evaluated. The grains were harvested mechanically, ground and immersed in water, adding the α-amylase enzyme, giving the must. The musts were submitted to inoculation by industrial yeast BG-1. The hybrids 2B587PW, 2B633PW and 2B810PW resulted in 3.65, 3.74 and 2.94 t ha-1 of grains, respectively. Average values of 430 L of ethanol recovered per processed were observed. It is concluded that the hybrid 2B633PW is the most suitable for the cultivation in the center-west of São Paulo state, because results in higher grain yield. The hybrids show differences in fermentative performance of BG-1 yeast, and the 2B810PW results in higher fermentation efficiency and the amount of ethanol produced per ton of processed corn.
Híbridos de Milho Afetam a Quantidade de Etanol Produzida no Cerrado do Centro-Oeste Paulista
Keywords: Bioenergy; Saccharomyces cerevisiae; Sucroenergetic Sector; Zea mays